Development of the Indonesian Capital Market After the Covid-19 Pandemic - Siti Nur Asiyah; Mulyani Muhaziroh; Devi Nur Irmawati (Peneliti.net, 2023)
The capital market is the means by which companies and other institutions (such as the state) are funded, as well as through investment activities. The impact of the COVID-19 pandemic on the capital market was marked by the fall of the JCI. The JCI for the January-June 2020 period was at -5% when compared to the previous year in the same period which was at its lowest level. In 2020-2022, the JCI is at the level of 5,979.07, 6,581.48, 7,182.96. The JCI for the January – June 2021 period grew by 10% when compared to the previous year in the same period. This study uses secondary data obtained from the publication of the Financial Services Authority (OJK). The data used consists of the JCI, market capitalization, transaction volume, trading value, total securities ownership, and investor growth from January 2019 - June 2022. This research is classified as a descriptive research type with a qualitative approach